Ribbed moraines in the Vopnafjörður region, Iceland - Erla Guðný Helgadóttir 1993- (2020)
Ice streams provide a primary drainage pathway for ice sheet mass loss. Studying palaeo-ice stream beds improves understanding of current ice streams‘ dynamics in modern ice sheets. This study sheds light on palaeo-ice streaming and deglaciation of the eastern part of the Iceland ice sheet (IIS). Palaeo-ice stream features are well preserved in the area, including streamlined bedforms and transverse bedforms known as ribbed moraines, which are the focus of this study. Ribbed moraines have not previously been described in Iceland and their origin and formation are highly debated. Ribbed moraines are often thought to indicate the transition zone between cold and warm based ice flow or fast and slow ice flow. Ribbed moraines located between estimated ice streaming and an ice divide west of Vopnafjörður are the subject of this study. They can potentially be linked to the onset of palaeo-ice streaming at the start of the highland plateau. This study reveals the sedimentology and architecture of ribbed moraines near Vopnafjörður and their morphological characteristics, distribution and spatial relationships. A model of formation was constructed for ribbed moraines in Hauksstaðaheiði. They are proposed to form as a result of extensional ice flow between the ice divide and ice streaming which pulls on ice in the transition zone. This would lead to the formation of extensional surface crevasses. Basal water saturated in sediments seeks lowest pressure underneath the transverse crevasses facilitating the stacking of blocks of subglacial material into transverse ridges. The ice stream shut down and became subject to passive retreat which was key to preservation of the ridges. This study has implications for improving the understanding and insight into the behavior of ice streaming in the northeast part of the IIS and sheds light on the role of ribbed moraines in palaeo- and modern ice sheets. Hraðskreiðir farvegir meginlandsjökla kallast ísstraumar. Þeir flytja mikið magn af ís og seti sem frá jöklunum kemur. Algengt er ...